Morphological assessment on day 4 and its prognostic power in selecting viable embryos for transfer. Issue 4 (9th September 2015) - Fabozzi, Gemma; Alteri, Alessandra; Rega, Emilia; Starita, Maria Flavia; Piscitelli, Claudio; Giannini, Pierluigi; Colicchia, Antonio
Summary: The aim of this study was to describe a system for embryo morphology scoring at the morula stage and to determine the efficiency of this model in selecting viable embryos for transfer. In total, 519 embryos from 122 patients undergoing intracytoplasmic sperm injection (ICSI) were scored retrospectively on day 4 according to the grading system proposed in this article. Two separate quality scores were assigned to each embryo in relation to the grade of compaction and fragmentation and their developmental fate was then observed on days 5 and 6. Secondly, the prediction value of this scoring system was compared with the prediction value of the traditional scoring system adopted on day 3. Morulas classified as grade A showed a significant higher blastocyst formation rate (87.2%) compared with grades B, C and D (63.8, 41.3 and 15.0%, respectively), ( P < 0.001). Furthermore, the ability to form top quality blastocysts was significantly higher for grade A morulas with respect to grades B, and C and D (37.8% vs. 22.4% vs. 11.1%), ( P < 0.001). Finally, the morula scoring system showed more prediction power with respect to the embryo scoring a value of 1 [Akaike information criterion (AIC) index 16.4 vs. 635.3 and Bayesian information criterion (BIC) index −68.8 vs. −30.0 for morulas and embryos respectively]. In conclusion, results demonstrated that the presented scoring system allows for the evaluation of eligible embryos for transfer as a significant correlation between the grade of morula, blastulation rate and blastocyst quality was observed. Furthermore, the morula scoring system was shown to be the best predictive model when compared with the traditional scoring system performed on day 3.